# Y(9y-1)=0

## Simple and best practice solution for Y(9y-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for Y(9y-1)=0 equation:

Simplifying
Y(9y + -1) = 0
Reorder the terms:
Y(-1 + 9y) = 0
(-1 * Y + 9y * Y) = 0
(-1Y + 9yY) = 0
Solving
-1Y + 9yY = 0
Solving for variable 'Y'.
Move all terms containing Y to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), 'Y'.
Y(-1 + 9y) = 0

#### Subproblem 1

Set the factor 'Y' equal to zero and attempt to solve: Simplifying Y = 0 Solving Y = 0 Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 0

#### Subproblem 2

Set the factor '(-1 + 9y)' equal to zero and attempt to solve: Simplifying -1 + 9y = 0 Solving -1 + 9y = 0 Move all terms containing Y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 9y = 0 + 1 9y = 0 + 1 Combine like terms: 0 + 1 = 1 9y = 1 Add '-9y' to each side of the equation. 9y + -9y = 1 + -9y Combine like terms: 9y + -9y = 0 0 = 1 + -9y Simplifying 0 = 1 + -9y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Y = {0}